Form, function and consequences of density dependence in a long‐distance migratory bird. Issue 3 (1st October 2013) - McKellar, Ann E.; Marra, Peter P.; Boag, Peter T.; Ratcliffe, Laurene M.
<x xml:space="preserve">Abstract</x> The density dependence of demographic parameters and its implications for population regulation have long been recognized. Recent work has revealed potential effects of density on mating systems and sexual selection, but few studies concurrently assess the consequences of density on both demography and sexual selection. Such an approach is important because population processes and individual behaviors can interact to influence population growth and evolutionary trajectories. In this study, we tested the density dependence of breeding success, extra‐pair paternity, and the opportunity for sexual selection in a population of American redstarts Setophaga ruticilla using two different measures of density. To evaluate temporal patterns, we analyzed annual territory density, based on the total number of territories at our study site each year. To evaluate spatial patterns, we analyzed local territory density within years, based on the number of territories surrounding a focal territory. Greater annual density was associated with fewer offspring fledged per female, a reduced mean population rate of fledging success, and a lower relative contribution of extra‐pair paternity to male fitness. Greater local density was associated with fewer offspring fledged, reduced fledgling success, higher rates of nest loss, and higher rates of paternity loss on focal territories. Interestingly, greater local density was also associated with greater nestling mass on focal territories, which could imply that more densely‐packed territories contain superior resources. Overall, our results suggest that the effects of crowding via greater territory density reduce fecundity through increased nest predation, rather than reduced food availability, and increase rates of extra‐pair paternity. Thus, the selective pressures faced by individuals and their reproductive behaviors are likely to differ based on the annual and local density they experience, which may then feed back into population demography.